The effect of high knee running and high knee bounce skips exercises on running speed of 100 meters of athletic extracurricular participants in senior high school - Listiwikono, Eko; Supono, Supono; Mustain, Ach Zayul; Setiawan, Wawan; Mursidi, Agus (Linguistics and Culture Review, 2022)
Field tennis is a small ball game that requires a field and the players need a racket with its own string specifications. Like the Wilson NXT brand strings on the Wilson Hyper Hamer 7.5 racket, which has its own tension when it will receive the ball. To find out the tension of the strings, it is necessary to do a test. The experiment was carried out on the Wilson Hyper Hamer 7.5 racket with Wilson NXT brand strings against the Wilson ball and Nassau ball bounce. This research is a quantitative descriptive in which the data are analyzed by performing normality test, homogeneity test, and hypothesis testing. The normality test carried out showed that the Wilson XT brand string tension on the Wilson Hyper Homer 7.5 racket against the Dunlop ball and Nassau ball bounce had a significance of 0.05 and was categorized as normal. For the homogeneity test, it can be seen that the results of the Dunlop ball and Nassau ball bounce have a sig value p (0.31) so that the data is homogeneous. From the results of the t-test is 8.133 and the t table is 2.31 with a p significance value of 0.611.